EFEK HEPATOPROTEKTOR EKSTRAK ETANOL RIMPANG DRINGO (Acorus calamus L.) TERHADAP PENINGKATAN KADAR SGPT TIKUS PUTIH (Rattus norvegicus) - Hendra Herman; Sitti Amirah; Triani Putri Ayu (As-Syifaa Jurnal Farmasi, 2018)
Hepatoprotector is a liver protected-agent of hepatotoxic. This research was aimed to determine the hepatoprotector effect of ethanol extract of dringo rhizome (Acorus calamus L.) and most effective dose as a hepatoprotector. The study using 20 male rats divided into 5 groups. Group I was given the Na-CMC 1%, group II was given a herbal supplement, and group III, IV, and V were given ethanol extract of the rhizome dringo (Acorus calamus L.) with a dose of 50 mg/100 mg, kgBB/kgBB, and 200 mg/kgBB orally for 7 days. At 5th day interval 2 hours after administering the test preparations were given a single dose of 2 g of paracetamol/kgBB in all groups except the Group I. Measurement of levels of SGPT is done before and after the treatment the animal test. From the results of a statistical analysis of Kruskal-Wallis’ test followed by Man-Whitney’s test that dringo Rhizome (Acorus calamus L.) ethanol extracts  has the effect of a hepatoprotector in rats. Extract 50 mg/kgBB dose has the same effect as statistically with herbal supplements’ group (˃ p 0.05).